(untitled) (Journal of Building and Road Research, 2021)
This paper investigates the effects of adding natural wadi sand to a typical unbound subbase material from Alsilait area in Khartoum. Four trials blends were prepared.Only two of the blends satisfied the (TRL, GB3) gradation and strength requirements of the unbound base course material. The strength, the stiffness and deformations characteristics were evaluated for the blends, using the CBR, resilient modulus (MR) and permanent deformation (PD) tests. Pavement physical models were constructed using the studied samples in the resilient modulus mould. The physical model comprises subgrade, sub-base, base course, and asphalt layer. The only variable in the physical model testing was the type of base course material. The model was subjected to dynamic loading typical to PD test conditions. The tests results have shown that the blends satisfying the GB3 base requirements measured the smallest values of permanent deformations. Minor differences were found for the PD values this also applies to the physical model tests. The study has shown that the large differences in CBR values did not result in large differences in permanent deformation and stiffness (MR) values.